Pengaruh Impor Garam terhadap Harga Garam dan Kemiskinan Petani Garam di Pulau Madura - Mohammad - Rofik; Anik Anekawati; Arief Hidayatullah Khamainy (Jurnal Ekonomi Pembangunan, 2022)
National salt needs are increasing along with population growth and industrial development. The significant demand for salt from various industrial use led to different standardization of salt products produced. Madura Island is one of the salt-producing centers. But high salt production of Madura is not followed by the welfare of salt farmers. Therefore, a scientific study is needed to be related to the relationship of salt imports to national salt prices and the poverty of salt farmers, especially on Madura Island. The results show that salt imports do not significantly correlate with domestic salt prices. The Increasing volume of salt imports (% tons) can trigger a decrease in the price of raw material salt in Indonesia in the next two years. This means that increasing the import of salt can reduce or damage the price of raw material salt in the future or incoming year. Salt Exchange Rate (SER) is used to measure the well-being of salt farmers. The results obtained show a negative relationship between SER and the number of salt imports. There is a negative relationship between the exchange rate of salt farmers and the number of salt imports. This shows that the higher the number of salt imports, the consistently smaller value of SER, or the higher amount of salt imports, the salt farmers will be in deficit.